Guidelines for the Management of Educational Learning Resources of School Under Phra Nakorn Si Ayutthaya Secondary Educational Service Area - Janpradab , Aadtapol; Techawattanasiridumrong , Wacharapatr; Montaisong, Teerawat (Journal of Dhamma for Life, 2025)
The purposes of this research were: (1) to examine the current conditions and problems of environmental management that promotes a learning-supportive atmosphere for students in educational institutions, and (2) to propose guidelines for managing such environments. This study employed a mixed methods research design and was conducted in two phases. Phase 1 involved quantitative research to investigate the conditions and problems of environmental management. The sample consisted of 298 teachers under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya, selected through stratified random sampling based on the Kreje and Morgan table. The research instrument was a questionnaire with a reliability coefficient of 0.90. Data were analyzed using descriptive statistics, including mean and standard deviation. Phase 2 involved qualitative research aimed at developing guidelines for environmental management that enhances the learning atmosphere. The key informants comprised seven administrators: two directors from secondary and primary educational service area offices and five school principals, selected through purposive sampling. The research instrument was an open-ended interview, and the data were analyzed using content analysis. The research findings revealed that: (1) the overall level of environmental management conditions and problems promoting a learning-supportive atmosphere in educational institutions was at a high level. Among the dimensions, safety had the highest mean score, followed by teaching and learning, while landscape management had the lowest mean score. (2) The guidelines for environmental management that promote a learning-supportive atmosphere consisted of six dimensions: facilities and buildings, landscape, safety, interpersonal interactions, teaching and learning, and management. These guidelines serve as essential strategies for improving educational environments that effectively and sustainably support student learning.